2019
DOI: 10.1016/j.jaci.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of galectin-3 as an autoantigen in patients with IgG4-related disease

Abstract: Affinity chromatography using patient-derived mAbs identifies relevant autoantigens in patients with IgG-RD. IgG galectin-3 autoantibodies are present in a subset of patients with IgG-RD and correlate with galectin-3 plasma levels. The marked increases in levels of circulating IgG and IgE observed clinically are, at least in part, caused by the development of IgG- and IgE-specific autoantibody responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 36 publications
2
81
0
12
Order By: Relevance
“…On the other hand, US scientists have identified galectin-3, a b-galactoside-binding lectin, as an autoantigen for IgG4-RD by immunoaffinity chromatography and mass spectrometry using plasma blast clones from IgG4-RD [29]. Some 28% of 121 patients with IgG4-RD were positive for anti-galectin-3 antibody.…”
Section: Do Autoantibodies To Self-antigens Cause Immunoglobin G4-relmentioning
confidence: 99%
“…On the other hand, US scientists have identified galectin-3, a b-galactoside-binding lectin, as an autoantigen for IgG4-RD by immunoaffinity chromatography and mass spectrometry using plasma blast clones from IgG4-RD [29]. Some 28% of 121 patients with IgG4-RD were positive for anti-galectin-3 antibody.…”
Section: Do Autoantibodies To Self-antigens Cause Immunoglobin G4-relmentioning
confidence: 99%
“…These observations suggest an important aspect of the pathogenesis of IgG4-RD, namely that the hyperproduction of IgG4 is frequently associated with allergy (32), suggesting a characteristic of allergic disease. Recently, both IgG4-and IgE-iso-type antibodies against galectin-3 produced by plasmablasts clones have been reported in patients with IgG4-RD (33). Although further investigation is required, the mechanism underlying isotype switching of immunoglobins to IgG4/IgE may be important in the pathogenesis of IgG4-RD (19).…”
Section: Igg4-related Hypophysitismentioning
confidence: 99%
“…Reactivity against multiple autoantigens in a subset of IgG4-RD patients. We previously reported that 28% of subjects from a cohort of 121 IgG4-RD patients had autoantibodies directed against galectin-3 (7). We examined the reactivity in patients in the present cohort who had data available regarding galectin-3 antibody responses (n = 86).…”
Section: Frequencies Of Annexin A11 and Laminin 511-e8mentioning
confidence: 99%
“…Since 2015, 4 autoantigens have been described as potential triggers for IgG4‐RD: prohibitin, annexin A11, laminin 511‐E8, and galectin‐3 . However, validation of these findings using external patient cohorts and characterization of the relationship between these specific autoantigens has yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation